2019
DOI: 10.1504/ijpqm.2019.096990
|View full text |Cite
|
Sign up to set email alerts
|

Business research productivity and barriers

Abstract: Knowing why some faculty members are more scholarly productive than others and what factors influence research productivity in an institution is essential to guiding research productivity improvement efforts. This study explored the research productivity and perceived research barriers to conducting research by the business faculty members at the Kuwait University (KU) as well as the influence of their individual characteristics on the reported productivity and barriers. The reported business research producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The significant effect of such research management practices thus implies that the absence of formal research teams and collaboration arrangements within the university could be a key predictor of the low research performance. The study findings were, therefore, in agreement with those of Nguyen et al (2016), Khalil and Khalil (2019), Kwiek (2018), Putri andSofyandi (2019) andVabo et al (2016), who found that research collaboration between colleagues at department and faculty levels provided peer support, especially in the form of training for younger and less experienced academics to improve their research skills, become more efficacious and motivated in addition to creating a supportive research culture for increased research outputs.…”
Section: Research Management and Research Productivitysupporting
confidence: 91%
See 1 more Smart Citation
“…The significant effect of such research management practices thus implies that the absence of formal research teams and collaboration arrangements within the university could be a key predictor of the low research performance. The study findings were, therefore, in agreement with those of Nguyen et al (2016), Khalil and Khalil (2019), Kwiek (2018), Putri andSofyandi (2019) andVabo et al (2016), who found that research collaboration between colleagues at department and faculty levels provided peer support, especially in the form of training for younger and less experienced academics to improve their research skills, become more efficacious and motivated in addition to creating a supportive research culture for increased research outputs.…”
Section: Research Management and Research Productivitysupporting
confidence: 91%
“…","non-dropping-particle":"","parse-names":false ,"suffix":""},{"dropping-particle":"","family":"Legazpe","given":"Nuria","non-dropping-particle-":"","parse-names":false,"suffix":""}],"container-title":"European Journal of Education","id":"ITEM-1","issue":"4","issued":{"date-parts": [["2016"]]},"page":"535-549","title":"Determinants of Research Productivity in Spanish Academia","type":"article-journal","volume":"51"},"uris":["http://www. mendeley.com/documents/?uuid=974a30c0-17a1-4de0-88fc-be9df282866f"]}],"mendeley":{"forma ttedCitation":" (Albert et al, 2016a;Alhija & Majdob, 2017;Hadre, Beesley, & Pace, 2018;Henry et al, 2020;Janib, Rasdi, Omar et al, 2021;Khalil & Khalil, 2019;Nguyen et al, 2016;Okendo, 2018;Putri & Sofyandi, 2019;Salman, Kausar, & Furqan, 2018;Starovoytova, 2017b;Zhang, Clayton, & Breznitz, 2019) who, without exception, indicated a negative relationship between time spent on teaching and lecturers' research output.…”
Section: Objectives Hypothesis and Questionsmentioning
confidence: 99%
“…The results confirm that the gender was not statistically significant in the production of research papers. Previous literature suggests that there is conflicting evidence on the influence of gender on individual research output (Khalil & Khalil, 2019). Similar results were found by Webber (2011), who concluded that female researchers have production levels similar to those of their male peers but that there could be differences according to the academic discipline, mainly because no distinctions have been made in terms of the academic disciplines of women.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies aim to explain the lower intellectual production of women throughout their careers caused by differences in family responsibilities, different patterns of time use, unequal resource allocation, different patterns in academic collaboration, and gender bias in peer-review (Sá et al, 2020). However, some studies contradict these results since they found that gender has no significant effect on research productivity indicators and women have production rates similar to their male peers (Khalil & Khalil, 2019). Moreover, previous studies show that there could be differences in research productivity by gender that depend on their academic fields.…”
Section: Individual Characteristics Of the Researchermentioning
confidence: 99%